2018
DOI: 10.21320/1818-474x-2018-2-79-86
|View full text |Cite
|
Sign up to set email alerts
|

Modern aspects of the relationship between the functional state of the autonomic nervous system and clinical and laboratory indices of the bodyʼs homeostasis in brain injuries

Abstract: A review of the literature is devoted to the analysis of the role of the autonomic nervous system as the main regulator of the body's homeostasis in heterotopic (anoxia, craniocerebral trauma, cerebral circulation disorder) brain damage. First of all, clinical, pathophysiological definitions and methods of pharmacological correction of manifestations of sympathetic and parasympathetic hyperactivity (paroxysmal sympathetic hyperactivity - PSH, paroxysmal parasympathetic hyperactivity - PPH) are considered first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 94 publications
0
3
0
Order By: Relevance
“…Research on other species of animals and humans revealed a direct and indirect effect of the parasympathetic system, and especially the centers in the brain on feelings of hunger and, consequently, the amount of food or food consumed (Grechko et al, 2018). Similar data on the meta-bolism of total protein and amino acids in animals were obtained in experiments on pigs (Trokoz et al, 2013), where the predominance of strong types of HNA determined a higher level of protein in the serum of pigs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on other species of animals and humans revealed a direct and indirect effect of the parasympathetic system, and especially the centers in the brain on feelings of hunger and, consequently, the amount of food or food consumed (Grechko et al, 2018). Similar data on the meta-bolism of total protein and amino acids in animals were obtained in experiments on pigs (Trokoz et al, 2013), where the predominance of strong types of HNA determined a higher level of protein in the serum of pigs.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the effect of increased tone of the parasympathetic division of the ANS, possibly through the humoral system (Shaikhelislamova et al, 2008) accelerates the catabolism of proteins and their use for the body. It was found that the influence of the parasympathetic division of the autonomic nervous system promotes the accumulation and absorption of nutrients from the intestine (Shields, 1993;Grechko et al, 2018), which is accompanied by a higher content of amino acsids in the serum of chickens compared to normotonics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation